Adaptation languages as vehicles of explicit intelligence in Adaptive Hypermedia. (7th September 2007) - Stash, Natalia; Cristea, Alexandra I.; De Bra, Paul
This paper deals with a new challenge in Adaptive Hypermedia (AH) and web-based systems: finding the adaptation language to express, independently from the domain model or platform, the intelligent, adaptive behaviour of personalised web courseware. The major requirements for the ideal language are: reuse, flexibility, high level semantics, and ease of use. To draw closer to this ideal language, we compare two such language proposals: LAG, a generic adaptation language, and a new XML adaptation language for Learning Styles (LS) in AHA!, LAG-XLS.